Urban Time and Rome’s Resilience: steeling Oneself against Disaster in Religious Practices - Rüpke, Jörg (Numen, 2019)
This article focuses on the relation of resilience and religion, using resilience as a lens for the analysis of religion and vice versa. By focusing on religious practices that might reasonably be seen as fostering resilience, I suggest that religious change in ancient Roman religion can be related to a constellation of material and social action that could be termed urban resilience. Among the very few historical data that allow the relating of specific religious practices to the ups and downs of urban history, an important source is preserved in the material — and frequently even monumental — form of calendars (fasti). I suggest that the development of some features of this cross-culturally exceptional material presence and graphic representation of a solar year and its rituals offer a glimpse into different forms of practices that might have reflected and helped foster urban resilience.